Curable resin composition, cured product, varnish, prepreg, and circuit board
By using a composition of a curable resin with a specific indan skeleton and a non-conjugated vinyl compound, the problem of insufficient heat resistance and dielectric properties of the curable resin in the prior art is solved, and cured substances with high glass transition temperature and low dielectric loss tangent are achieved, and electrically insulating materials are suitable for high frequency bands.
Patent Information
- Application Number
- CN202411275069.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-27
- Filing Date
- 2024-09-12
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art still has shortcomings in improving the heat resistance and dielectric properties of curable resins, especially in terms of transmission loss and heat resistance requirements in high frequency bands, and existing materials are difficult to meet high performance requirements.
The heat resistance and dielectric properties of the curable resin having a specific indan skeleton and a compound containing a non-conjugated vinyl group bonded to a non-aromatic group are improved by crosslinking an ester group structure with a (meth)acryloyl group.
The high glass transition temperature and low dielectric loss tangent of the cured substance are achieved, which significantly improves the heat resistance and dielectric properties of the material, and is suitable for electrical insulating materials in high frequency bands.
Smart Images

Figure CN119899346A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a curable resin composition, and a cured product, a varnish, a prepreg and a circuit board obtained by using the curable resin composition. Background Art
[0002] With the increase in the amount of information communication in recent years, information communication in high frequency bands has become prevalent, and there is a demand for electrical insulating materials with better electrical properties, especially low dielectric constants and low dielectric loss tangents in order to reduce transmission losses in high frequency bands.
[0003] Furthermore, printed circuit boards or electronic components using these electrical insulating materials are exposed to high-temperature reflow soldering during actual installation, so materials with excellent heat resistance and a high glass transition temperature are required. In particular, from the perspective of environmental issues, lead-free solders with high melting points are used recently, and the demand for electrical insulating materials with higher heat resistance is increasing.
[0004] In response to these requirements, curable resins containing vinyl groups having various chemical structures have been proposed in the past. Examples of such curable resins include divinylbenzyl ether of bisphenol and polyvinylbenzyl ether of novolac (see, for example, Patent Documents 1 and 2).
[0005] Regarding vinyl benzyl ether having improved properties as described above, several polyvinyl benzyl ethers having specific structures have been proposed in order to achieve improvement in dielectric properties and the like (for example, refer to Patent Documents 3 to 5).
[0006] Furthermore, in order to improve heat resistance and dielectric properties, curable resins having a specific indane skeleton have been proposed (for example, Patent Document 6).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 63-68537
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 64-65110
[0011] Patent Document 3: Japanese Patent Publication No. 1-503238
[0012] Patent Document 4: Japanese Patent Application Laid-Open No. 9-31006
[0013] Patent Document 5: Japanese Patent Application Publication No. 2005-314556
[0014] Patent Document 6: International Publication No. 2021 / 205806 Summary of the invention
[0015] Problems to be solved by the invention
[0016] In this way, attempts have been made to suppress the dielectric loss tangent and to improve the heat resistance. However, the technologies of Patent Documents 1 to 5 cannot be said to have sufficiently improved these characteristics. In addition, the technology of Patent Document 6 is also expected to further improve the heat resistance.
[0017] Therefore, an object of the present invention is to provide a curable resin composition capable of obtaining a cured product having excellent heat resistance (high glass transition temperature) and dielectric properties (low dielectric properties).
[0018] Means for solving problems
[0019] Therefore, the present inventors conducted intensive studies to solve the above-mentioned problems, and as a result, found that the cured product obtained from a curable resin composition containing a curable resin having a specific indane skeleton and a compound containing a non-conjugated vinyl group bonded to a non-aromatic group has excellent heat resistance (high glass transition temperature) and dielectric properties (low dielectric properties), thereby completing the present invention.
[0020] That is, the gist of the present invention is as follows.
[0021] [1] A curable resin composition comprising a curable resin (A) having an indane skeleton represented by the following general formula (1), and a compound (B) comprising a non-conjugated vinyl group bonded to a non-aromatic cyclic group,
[0022] [Chemistry 1]
[0023]
[0024] In the above formula (1), X represents a (meth)acryloyl group. Ra and Rb are each independently an alkyl group, an aryl group, an aralkyl group or a cycloalkyl group having 1 to 12 carbon atoms, j represents an integer of 1 to 3, and k and l each independently represent an integer of 0 to 4. n is the average number of repeating units, representing a value of 0.5 to 20, and m represents an integer of 0 to 2. The straight line from Ra, X and the carbon atom to the aromatic ring represents any site that can be bonded to the aromatic ring.
[0025] [2] The curable resin composition according to [1], wherein (A) is a curable resin having an indane skeleton represented by the following general formula (2):
[0026] [Chemistry 2]
[0027]
[0028] In the above formula (2), R1 and R2 are independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an aryl group, an aralkyl group or a cycloalkyl group, and R1 and R2 are not both hydrogen atoms at the same time. n is the average number of repeating units and represents a value of 0.5 to 20.
[0029] [3] The curable resin composition according to [1] or [2], wherein (B) is a butadiene polymer containing a 1,2-butadiene unit having a 1,2-vinyl group in a side chain in the molecule.
[0030] [4] The curable resin composition according to any one of [1] to [3], wherein (B) is a compound having two or more allyl groups.
[0031] [5] The curable resin composition according to any one of [1] to [4], wherein the mass of (B) is 5 to 40 parts by mass relative to 100 parts by mass of the total mass of (A) and (B).
[0032] [6] A cured product obtained by subjecting the curable resin composition according to any one of [1] to [5] to a curing reaction.
[0033] [7] A varnish obtained by diluting the curable resin composition according to any one of [1] to [5] with an organic solvent.
[0034] [8] A prepreg comprising a reinforcing base material and a semi-cured product of the varnish described in [7] impregnated into the reinforcing base material.
[0035] [9] A circuit board obtained by laminating the prepreg described in [8] and copper foil and then heat-compression-bonding them.
[0036] Effects of the Invention
[0037] The curable resin composition of the present invention is useful because it can provide a cured product having excellent heat resistance (high glass transition temperature) and dielectric properties (low dielectric properties). DETAILED DESCRIPTION
[0038] Hereinafter, the present invention will be described in detail.
[0039] <Curable Resin Composition>
[0040] [Curing resin (A)]
[0041] The curable resin composition of the present invention contains a curable resin (A) having an indane skeleton represented by the following general formula (1).
[0042] [Chemistry 3]
[0043]
[0044] In the above formula (1), X represents a (meth)acryloyl group. Ra and Rb are each independently an alkyl group, an aryl group, an aralkyl group or a cycloalkyl group having 1 to 12 carbon atoms, j represents an integer of 1 to 3, and k and l each independently represent an integer of 0 to 4. n is the average number of repeating units, and represents a value of 0.5 to 20. m represents an integer of 0 to 2. The straight line from Ra, X and the carbon atom to the aromatic ring represents any site that can be bonded to the aromatic ring.
[0045] The curable resin (A) has a low polar indane skeleton, thereby reducing the proportion of polar functional groups in the structure of the curable resin, and the dielectric properties of the cured product produced using the curable resin are excellent, so it is preferred. In addition, the curable resin (A) has an indane skeleton, thereby having excellent flexibility and softness, and it is also expected that the improvement of brittleness resistance can be improved, which is preferred.
[0046] In the above formula (1), X is a (meth)acryloyl group that becomes a crosslinking group, that is, an acryloyl group or a methacryloyl group, and a methacryloyl group is particularly preferred. By having a (meth)acryloyl group in the curable resin, a cured product having a low dielectric loss tangent can be obtained compared with other crosslinking groups (such as vinyl benzyl ether group (styryl group), dihydroxyphenyl group, etc.), which is a preferred embodiment.
[0047] It should be noted that the detailed reason why a cured product exhibiting low dielectric properties can be obtained by having the (meth)acryloyl group is not clear, but it is speculated that in the case of a vinylbenzyl ether group (styryl group) or the like contained in a curable resin used in the past, an ether group is present as a polar group, and in the case of a dihydroxyphenyl group, a plurality of hydroxyl groups are present as polar groups, and as in the curable resin (A) of the present invention, an ester group based on a (meth)acryloyl group has low molecular mobility, which is more advantageous (when having a highly polar group such as an ether group or a hydroxyl group, there is a tendency for the dielectric constant and the dielectric loss tangent to become higher).
[0048] In addition, when the crosslinking group is a methacryloyl group, it is speculated that since the structure contains a methyl group, the steric hindrance becomes larger, the molecular mobility is further reduced, and a cured product with a lower dielectric loss tangent can be obtained, which is preferred. In addition, when there are multiple crosslinking groups, the crosslinking density is increased and the heat resistance is improved.
[0049] In the above formula (1), Ra independently represents an alkyl group, an aryl group, an aralkyl group or a cycloalkyl group having 1 to 12 carbon atoms, preferably an alkyl group, an aryl group or a cycloalkyl group having 1 to 4 carbon atoms. By using the alkyl group having 1 to 12 carbon atoms, the planarity near any of the benzene ring, naphthalene ring and anthracene ring described later is reduced, the crystallinity is reduced, thereby improving the solvent solubility, and the melting point is lowered, which becomes a preferred mode. In addition, it is speculated that by having the Ra, it becomes a steric hindrance, the molecular mobility is further reduced, and a cured product with a lower dielectric loss tangent can be obtained, so it is preferred.
[0050] In the above formula (1), Rb each independently represents an alkyl group, aryl group, aralkyl group or cycloalkyl group having 1 to 12 carbon atoms, preferably an alkyl group, aryl group or cycloalkyl group having 1 to 4 carbon atoms. By using the alkyl group having 1 to 12 carbon atoms, the planarity near any of the benzene ring, naphthalene ring and anthracene ring described later is reduced, the crystallinity is reduced, and the solvent solubility is improved, and the melting point is lowered, which is a preferred embodiment.
[0051] In the above formula (1), j represents an integer of 1 to 3, preferably an integer of 1 to 2. By being within the above range, flexibility can be ensured, which is a preferred embodiment. It should be noted that by introducing multiple Xs that become cross-linking groups into the same benzene ring, etc., multiple cross-linking groups hinder (mutually inhibit) molecular mobility, and even in the absence of the above Ra as a substituent, a cured product showing a low dielectric loss tangent can be obtained, which is preferred.
[0052] In the above formula (1), k and l each independently represent an integer of 0 to 4, preferably an integer of 0 to 2. When it is within the above range, the reactivity is excellent, which is a preferred embodiment.
[0053] In the above formula (1), m represents an integer of 0 to 2, that is, when m is 0, it is a benzene ring, when m is 1, it is a naphthalene ring, and when m is 2, it is an anthracene ring, and preferably, m is 0. Within the above range, solvent solubility is excellent, which is a preferred embodiment.
[0054] In the above formula (1), n is the average number of repeating units, which represents a value of 0.5 to 20, preferably 0.5 to 5, and more preferably 0.95 to 2.5. By having an indane skeleton within the above range, the solvent solubility is excellent, which becomes a preferred mode. It should be noted that if the n is less than 0.5, the content ratio of the high melting point substance in the structure of the curable resin having the indane skeleton becomes high, the solvent solubility is poor, and the proportion of the high molecular weight component that contributes to flexibility becomes low, so the brittleness resistance of the obtained cured product is reduced, and the flexibility and softness may also be reduced, which is not preferred. In addition, if the n exceeds 20, there is a concern that the viscosity becomes high when dissolved in a solvent, and the heat resistance of the obtained cured product deteriorates, and there is a concern that the high molecular weight component becomes too much, which reduces the fluidity during the molding of the cured product and deteriorates the handling property, which is not preferred. In addition, as the value of the n, from the viewpoints of the high heat deformation temperature and high glass transition temperature of the cured product, 0.95 to 2.5 is particularly preferred.
[0055] By providing the curable resin (A) with an indane skeleton, an alicyclic structure having an excellent balance between heat resistance and dielectric properties is introduced into the structure of the curable resin, and a cured product produced using the curable resin has an excellent balance between heat resistance and dielectric properties (particularly low dielectric loss tangent). Furthermore, by having a (meth)acryloyl group that serves as a cross-linking group in the molecular structure, steric hindrance is increased, and further low dielectric properties can be exhibited, which is preferred.
[0056] Furthermore, the curable resin (A) in the present invention preferably has an indane skeleton represented by the following general formula (2).
[0057] [Chemistry 4]
[0058]
[0059] In the above formula (2), R1 and R2 are independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an aryl group, an aralkyl group or a cycloalkyl group, and R1 and R2 are not both hydrogen atoms at the same time. n is the average number of repeating units and represents a value of 0.5 to 20.
[0060] In the above formula (2), R1 and R2 are independently a hydrogen atom, an alkyl group, an aryl group, an aralkyl group or a cycloalkyl group having 1 to 12 carbon atoms, and both are not hydrogen atoms at the same time, preferably an alkyl group, an aryl group or a cycloalkyl group having 1 to 4 carbon atoms. By using the alkyl group having 1 to 12 carbon atoms, the planarity near the benzene ring is reduced, the crystallinity is reduced, and thus the solvent solubility is improved, and the melting point is lowered, which becomes a preferred mode. In addition, by having the R1 and R2, it is speculated that the steric hindrance becomes larger (but in the case of non-hydrogen atoms), the molecular mobility is further reduced, and a cured product with a lower dielectric loss tangent can be obtained, so it is preferred.
[0061] In the above formula (2), n is the average number of repeating units, which represents a value of 0.5 to 20, preferably 0.5 to 5, and more preferably 0.95 to 2.5. By having an indane skeleton within the above range, the solvent solubility is excellent, which becomes a preferred mode. It should be noted that if the n is less than 0.5, the content ratio of the high melting point substance in the structure of the curable resin (A) becomes high, the solvent solubility is poor, and the proportion of the high molecular weight component that contributes to flexibility becomes low, so the brittleness resistance of the obtained cured product is reduced, and the flexibility and softness may also be reduced, which is not preferred. In addition, if the n exceeds 20, there is a concern that the viscosity becomes high when dissolved in a solvent, and the heat resistance of the obtained cured product deteriorates, and there is a concern that the high molecular weight component becomes too much, which reduces the fluidity during the molding of the cured product and deteriorates the handling property, which is not preferred. In addition, as the value of the n, from the viewpoint of the high heat deformation temperature and high glass transition temperature of the cured product, 0.95 to 2.5 is particularly preferred.
[0062] The softening point of the curable resin (A) is preferably 150° C. or less, and more preferably 30 to 100° C. When the softening point of the curable resin (A) is within the above range, processability is excellent, which is preferred.
[0063] The curable resin (A) may be used alone or in combination of two or more in any ratio.
[0064] The curable resin (A) can be produced by the production method described in International Publication No. 2021 / 205806.
[0065] [Compound (B) containing a non-conjugated vinyl group bonded to a non-aromatic cyclic group]
[0066] The curable resin composition of the present invention contains a compound (B) having a non-conjugated vinyl group (hereinafter also referred to as a "predetermined vinyl group") bonded to a non-aromatic cyclic group.
[0067] The compound (B) in the present invention is characterized in that it has one or more vinyl groups, which do not form a conjugated system and are not directly bonded to the ring-forming atoms of the aromatic cyclic group. A non-conjugated vinyl group refers to a vinyl group that does not form a conjugated system, and bonding to a non-aromatic cyclic group means bonding to the chain group when the non-aromatic cyclic group is a chain group, and directly bonding to the ring-forming atoms of the cyclic group when the non-aromatic cyclic group is a cyclic group.
[0068] The compound (B) in the present invention is not particularly limited as long as it has one or more predetermined vinyl groups, but preferably has two or more predetermined vinyl groups from the aspects of reactivity and heat resistance of the cured product. The compound (B) may contain, for example, 50 or less predetermined vinyl groups.
[0069] As compound (B), from the viewpoint of heat resistance, a butadiene polymer (hereinafter also referred to as "prescribed butadiene polymer") containing a 1,2-butadiene unit having a 1,2-vinyl group in a side chain (hereinafter also referred to as "1,2-butadiene unit") is preferred. The 1,2-butadiene unit having a 1,2-vinyl group in a side chain corresponds to a 1,2-adduct of butadiene and includes a unit represented by the following formula (3).
[0070] [Chemistry 5]
[0071]
[0072] The compound (B) may be a homopolymer composed of only 1,2-butadiene units or a copolymer composed of 1,2-butadiene units and repeating units other than the 1,2-butadiene units. The copolymer may be a random polymer or a block polymer.
[0073] In the case of a copolymer, it is preferred that 20% by weight or more of 1,2-butadiene units be contained. From the viewpoint of expressing the effects of introducing other repeating units, the 1,2-butadiene units are preferably contained at most 80% by weight, more preferably at most 70% by weight.
[0074] The repeating units other than the 1,2-butadiene unit (hereinafter also referred to as "other repeating units") are not particularly limited, but examples thereof include units represented by the following formula (4) which are equivalent to 1,4-adducts of 1,3-polybutadiene.
[0075] [Chemistry 6]
[0076]
[0077] The other repeating units may be units derived from a diene other than butadiene, and examples of such units include units derived from 1,4-pentadiene, 1,5-hexadiene, 1,6-heptadiene, 1,7-octadiene, 1,8-nonadiene, and the like.
[0078] Other repeating units may be units derived from olefins and derivatives thereof, and examples of such units include units derived from ethylene, propylene, and the like.
[0079] Other repeating units may be units derived from styrene and derivatives thereof. Examples of such units include units derived from styrene, vinyltoluene, divinylbenzene, and the like.
[0080] The specified butadiene polymers may be modified with maleic acid.
[0081] The prescribed butadiene polymer is preferably a copolymer comprising prescribed butadiene units and styrene units.
[0082] From the viewpoint of fluidity and compatibility, the number average molecular weight (Mn) of the predetermined butadiene polymer is preferably 500 to 100,000, more preferably 500 to 50,000, and even more preferably 800 to 10,000.
[0083] Examples of the specified butadiene polymer include Cray Valley butadiene-styrene random copolymers (Ricon 100, Ricon 110, Ricon 181, Ricon 184), polybutadiene-styrene-divinylbenzene graft terpolymers (Ricon 257), and 1,3-polybutadiene homopolymers (B series, B-1000, B-2000, B-3000) manufactured by Nippon Soda Co., Ltd.
[0084] As the compound (B), from the viewpoint of heat resistance, a compound having two or more allyl groups (CH2=CH-CH2-) (hereinafter also referred to as "allyl compound") is preferred.
[0085] Examples of the allyl compound include triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), diallyl phthalate, and triallyl trimellitate. From the viewpoint of dielectric properties, TAIC is preferred.
[0086] The compound (B) may be used alone or in combination of two or more in any ratio.
[0087] [Amount]
[0088] The curable resin composition of the present invention contains a curable resin (A) having an indane skeleton represented by the general formula (1) and a compound (B) comprising a non-conjugated vinyl group bonded to a non-aromatic ring group. By combining these, a cured product having excellent heat resistance (high glass transition temperature) and dielectric properties (low dielectric properties) can be obtained.
[0089] Regarding the mass of the curable resin (A) and the mass of the compound (B), from the perspective of achieving both excellent heat resistance and excellent dielectric properties, the mass of (B) is preferably 5 to 40 parts by mass, and particularly preferably 8 to 35 parts by mass, relative to 100 parts by mass of the total mass of (A) and (B).
[0090] [Other resins, etc.]
[0091] In the curable resin composition of the present invention, a resin component can be mixed within a range that does not impair the purpose. For example, as the resin component, a thermoplastic elastomer can be cited. In addition, maleimide resin, thermosetting polyimide resin, epoxy resin, phenolic resin, active ester resin, benzoxazine resin, cyanate resin, etc. can also be appropriately mixed according to the purpose.
[0092] [Curing agent]
[0093] The curable resin composition of the present invention may contain a curing agent. Examples of the curing agent include amine compounds, amide compounds, anhydride compounds, benzene compounds, cyanate compounds, etc. These curing agents may be used alone or in combination of two or more in any ratio.
[0094] [Curing accelerator]
[0095] In the curable resin composition of the present invention, it is also possible to suitably and concurrently use a curing accelerator as required. As the curing accelerator, various curing accelerators can be used, for example, phosphorus compounds, tertiary amines, imidazoles, organic acid metal salts, Lewis acids, amine complex salts etc. can be enumerated. Particularly in the case of being used as semiconductor sealing material purposes, from the excellent aspects such as curability, heat resistance, electrical characteristics, moisture-proof reliability, phosphorus compounds such as preferred triphenylphosphine or imidazoles. These curing accelerators can be independent, and can also be the combination of more than 2 kinds of arbitrary ratios.
[0096] [Flame retardant]
[0097] In the curable resin composition of the present invention, a non-halogen flame retardant substantially free of halogen atoms can be formulated as needed to exert flame retardancy. Examples of the non-halogen flame retardant include phosphorus flame retardants, nitrogen flame retardants, silicone flame retardants, inorganic flame retardants, and organic metal salt flame retardants. These can be used alone or in combination of two or more at any ratio.
[0098] [Bulking Agent]
[0099] In the curable resin composition of the present invention, fillers can be added as needed. As fillers, inorganic fillers can be listed, for example, fused silica, crystalline silica, alumina, silicon nitride, aluminum hydroxide, etc. can be listed. In the case of particularly increasing the amount of the inorganic filler, fused silica is preferably used. The fused silica can be used in any of a crushed shape and a spherical shape. In order to increase the amount of fused silica and suppress the rise in the melt viscosity of the molding material, it is preferred to mainly use spherical fused silica. In order to further increase the amount of spherical silica, it is preferred to appropriately adjust the particle size distribution of spherical silica. In addition, when the curable resin composition is used for purposes such as the conductive paste described in detail below, conductive fillers such as silver powder and copper powder can be used.
[0100] [Other compounding ingredients]
[0101] The curable resin composition of the present invention may contain various compounding agents such as a silane coupling agent, a release agent, a pigment, and an emulsifier as necessary.
[0102] The curable resin composition of the present invention can be prepared by adding the curable resin (A), the compound (B), and, if necessary, the above-mentioned optional components and uniformly mixing them.
[0103] <Cured product>
[0104] The present invention also relates to a cured product obtained by subjecting the curable resin composition of the present invention to a curing reaction. The method of the curing reaction is not particularly limited and can be carried out by a conventionally known method. As the cured product, a laminate, a casting, an adhesive layer, a coating, a film, and other shaped cured products can be listed.
[0105] Examples of the curing reaction include heat curing and ultraviolet curing reactions. Among them, heat curing reactions are easy to carry out even without a catalyst, but when a faster reaction is desired, it is effective to add a polymerization initiator such as an organic peroxide or an azo compound. Examples include benzoyl peroxide, diisopropylbenzene peroxide, and azobisisobutyronitrile.
[0106] <Purpose>
[0107] The cured product obtained by the curable resin composition of the present invention is excellent in heat resistance (high glass transition temperature) and dielectric properties (low dielectric properties), so it can be suitable for heat-resistant components and electronic components. It can be particularly suitable for prepregs, circuit boards, semiconductor sealing materials, semiconductor devices, build-up films, build-up substrates, adhesives, resist materials, etc. In addition, it can also be suitable for the matrix resin of fiber-reinforced resins, and is particularly suitable as a high heat-resistant prepreg. In addition, the curable resin with the indane skeleton contained in the curable resin composition shows excellent solubility in various solvents, so it can be coated. The heat-resistant components and electronic components obtained in this way can be suitably used for various purposes, such as industrial machinery parts, general machinery parts, automobile / railway / vehicle parts, aerospace / aviation related parts, electronic / electrical parts, building materials, container / packaging components, daily necessities, sports / leisure products, shell components for wind power generation, etc., but are not limited to these.
[0108] Hereinafter, typical products produced using the curable resin composition of the present invention will be described with reference to examples.
[0109] [Varnish]
[0110] The present invention relates to a varnish, which is a material obtained by diluting the curable resin composition with an organic solvent. As a method for preparing the varnish, a known method can be used, and the curable resin composition can be dissolved (diluted) in an organic solvent to prepare a resin varnish. The present invention is advantageous in that the resin varnish has excellent non-tackiness and is obtained in a state where the resin varnish is desolvated (uncured or semi-cured) and the tackiness is suppressed.
[0111] As the organic solvent, for example, toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, methyl ethyl ketone (MEK), methyl isobutyl ketone, dioxane, tetrahydrofuran, etc. can be used alone or as a mixed solvent of two or more.
[0112] [Prepreg]
[0113] The present invention relates to a prepreg, which comprises a reinforcing substrate and a semi-cured product of the varnish impregnated in the reinforcing substrate. The varnish (resin varnish) is impregnated in the reinforcing substrate, and the reinforcing substrate impregnated with the varnish (resin varnish) is heat-treated, thereby making the curable resin composition semi-cured (or uncured) to prepare a prepreg.
[0114] The reinforcing substrate impregnated with the varnish (resin varnish) is a woven fabric, a nonwoven fabric, a mat, or a paper made of inorganic fibers such as glass fibers, polyester fibers, and polyamide fibers, or organic fibers, and these can be used alone or in combination.
[0115] The mass ratio of the curable resin composition to the reinforcing substrate in the prepreg is not particularly limited, but is generally preferably prepared so that the curable resin composition (resin component therein) in the prepreg is 20 to 60 mass %.
[0116] The heat treatment conditions for the prepreg are appropriately selected depending on the type and amount of the organic solvent, catalyst, and various additives used, and are generally carried out at a temperature of 80 to 220° C. for 3 to 30 minutes.
[0117] [Circuit board]
[0118] The present invention relates to a circuit substrate obtained by laminating the prepreg and copper foil and heat-compression molding. Specifically, as a method for obtaining a circuit substrate from the curable resin composition of the present invention, the prepreg can be laminated by a conventional method, copper foil can be appropriately overlapped, and heat-compression molding can be performed at 170 to 300° C. for 10 minutes to 3 hours under a pressure of 1 to 10 MPa to prepare a circuit substrate.
[0119] [Semiconductor sealing materials]
[0120] As a semiconductor sealing material, it is preferred to contain the curable resin composition. Specifically, as a method for obtaining a semiconductor sealing material from the curable resin composition of the present invention, it can be cited that in the curable resin composition, an extruder, a kneader, a roller, etc. are further used as needed to fully melt and mix the inorganic filler and other compounding agents as any component to a uniform method. At this time, as an inorganic filler, fused silica is generally used, but in the case of being used as a high thermal conductivity semiconductor sealing material for power transistors and power ICs, crystalline silica, alumina, silicon nitride, etc. having a thermal conductivity higher than that of fused silica can be used. Regarding its filling rate, relative to 100 parts by mass of the curable resin composition, it is preferred to use an inorganic filler in the range of 30 to 95 parts by mass, wherein, in order to achieve the improvement of flame retardancy, moisture resistance, resistance to solder cracking, and the reduction of the linear expansion coefficient, it is more preferably 70 parts by mass or more, and more preferably 80 parts by mass or more.
[0121] [Semiconductor devices]
[0122] As a semiconductor device, it is preferred to include a cured product formed by heating and curing the semiconductor sealing material. Specifically, as a semiconductor encapsulation molding of a semiconductor device obtained from the curable resin composition of the present invention, the following method can be cited: the semiconductor sealing material is cast, or molded using a transfer molding machine, an injection molding machine, etc., and then heated and cured at 50 to 250° C. for 2 to 10 hours.
[0123] [Build-up substrate]
[0124] As a method for obtaining a build-up substrate from the curable resin composition of the present invention, a method via steps 1 to 3 can be cited. In step 1, first, the curable resin composition appropriately mixed with rubber, filler, etc. is applied to a circuit substrate formed with a circuit by spraying, curtain coating, etc., and then cured. In step 2, after opening a predetermined through-hole portion or the like on the circuit substrate coated with the curable resin composition as needed, it is treated with a roughening agent, and its surface is washed with hot water to form unevenness on the substrate, and a plating treatment of metals such as copper is performed. In step 3, the operations of steps 1 to 2 are repeated in sequence as needed, and the resin insulating layer and the conductor layer of the predetermined circuit pattern are alternately layered to obtain a build-up substrate. It should be noted that in the process, the opening of the through-hole portion can be performed after the outermost resin insulating layer is formed. In addition, the build-up substrate in the present invention can also be made by heating and pressing the resin-coated copper foil obtained by semi-curing the resin composition on the copper foil at 170 to 300° C. onto a wiring substrate formed with a circuit, thereby omitting the steps of forming a roughened surface and plating treatment.
[0125] [Build-up film]
[0126] As a build-up film, it is preferred to contain the curable resin composition. As a method for obtaining a build-up film from the curable resin composition of the present invention, for example, a method of coating the curable resin composition on a support film, drying it, and forming a resin composition layer on the support film can be cited. In the case of using the curable resin composition of the present invention for a build-up film, it is important that the film softens under the lamination temperature conditions (usually 70 to 140° C.) in a vacuum lamination method, and exhibits fluidity (resin flow) that enables resin filling in vias or through holes present in the circuit substrate while laminating the circuit substrate, and it is preferred to combine the components to exhibit such characteristics.
[0127] Here, the through hole of the circuit board usually has a diameter of 0.1 to 0.5 mm and a depth of 0.1 to 1.2 mm, and it is usually preferable to fill the resin within this range. When laminating both sides of the circuit board, it is preferable to fill about 1 / 2 of the through hole.
[0128] As a specific method for manufacturing the above-mentioned build-up film, the following method can be listed: after preparing a varnished resin composition by mixing with an organic solvent, the varnished resin composition is coated on the surface of a support film (Y), and the organic solvent is dried by heating or blowing hot air to form a resin composition layer (X).
[0129] As the organic solvent used here, for example, ketones such as acetone, methyl ethyl ketone, and cyclohexanone, acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate, carbitols such as cellosolve and butyl carbitol, aromatic hydrocarbons such as toluene and xylene, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, etc. are preferably used. In addition, it is preferably used in a ratio of 30 to 60% by mass of non-volatile components.
[0130] It should be noted that the thickness of the formed resin composition layer (X) usually needs to be greater than the thickness of the conductor layer. The thickness of the conductor layer of the circuit substrate is usually in the range of 5 to 70 μm, so the thickness of the resin composition layer (X) preferably has a thickness of 10 to 100 μm. It should be noted that the resin composition layer (X) in the present invention can be protected by a protective film described later. By protecting with a protective film, dust and the like can be prevented from adhering to and damaging the surface of the resin composition layer.
[0131] The support film and the protective film can include polyolefins such as polyethylene, polypropylene, polyvinyl chloride, polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate, polycarbonate, polyimide, and metal foils such as release paper, copper foil, and aluminum foil. It should be noted that in addition to implementing matte treatment and corona treatment, the support film and the protective film can also be subjected to demolding treatment. The thickness of the support film is not particularly limited, and is generally 10 to 150 μm, preferably used in the range of 25 to 50 μm. In addition, the thickness of the protective film is preferably 1 to 40 μm.
[0132] The support film (Y) is peeled off after being laminated on a circuit board or after forming an insulating layer by heat curing. If the support film (Y) is peeled off after the resin composition layer constituting the build-up film is heat cured, it is possible to prevent the adhesion of dust and the like during the curing process. In the case of peeling off after curing, the support film is usually subjected to a demolding treatment in advance.
[0133] It should be noted that a multilayer printed circuit board can be manufactured from the build-up film obtained as described above. For example, when the resin composition layer (X) is protected by a protective film, after peeling them off, the resin composition layer (X) is laminated on one or both sides of the circuit substrate in a manner that is in direct contact with the circuit substrate by, for example, vacuum lamination. The lamination method may be intermittent or continuous using a roller. In addition, as needed, the build-up film and the circuit substrate may be heated (preheated) as needed before lamination. The lamination conditions preferably set the pressing temperature (lamination temperature) to 70 to 140°C, and preferably set the pressing pressure to 1 to 11 kgf / cm 2 (9.8×10 4 ~107.9×10 4 N / m2 ) It is preferably carried out under reduced pressure with an air pressure of 20 mmHg (26.7 hPa) or less for lamination.
[0134] [Conductive paste]
[0135] As a method for obtaining a conductive paste from the curable resin composition of the present invention, for example, a method of dispersing conductive particles in the composition can be cited. The above-mentioned conductive paste can be made into a paste resin composition for circuit connection or an anisotropic conductive adhesive according to the type of conductive particles used.
[0136] Examples
[0137] Next, the present invention will be specifically described by way of examples and comparative examples. Hereinafter, unless otherwise specified, "parts" and "%" are based on mass. It should be noted that the curable resin is synthesized under the conditions shown below. In addition, a curable resin composition containing the curable resin is prepared, and further a cured product is prepared by the curing reaction of the curable resin composition. For the curable resin and the cured product, measurement or calculation is carried out under the conditions shown below for evaluation.
[0138] <GPC measurement (evaluation of number average molecular weight (Mn) and average number of repeating units)>
[0139] Measurement is carried out using the following measurement apparatus and measurement conditions, and a GPC chart (not shown) of the curable resin is obtained by the synthesis method shown below. The number average molecular weight (Mn) of the curable resin is calculated from the results of the GPC chart. In addition, based on Mn, the average number of repeating units n contributing to the indane skeleton in the curable resin is calculated. Specifically, for compounds with n from 0 to 4, the theoretical molecular weight and the measured molecular weight in GPC are plotted on a scatter diagram, an approximate straight line is drawn, and the number average molecular weight (Mn) is obtained from the point indicated by the measured value Mn(1) on the straight line, and the average number of repeating units n is calculated.
[0140] Measurement apparatus: "HLC-8320GPC" manufactured by Tosoh Corporation
[0141] Column: Guard column "HXL-L" manufactured by Tosoh Corporation + "TSK-GEL G2000HXL" manufactured by Tosoh Corporation + "TSK-GEL G2000HXL" manufactured by Tosoh Corporation + "TSK-GEL G3000HXL" manufactured by Tosoh Corporation + "TSK-GEL G4000HXL" manufactured by Tosoh Corporation
[0142] Detector: RI (differential refractometer)
[0143] Data processing: Tosoh Corporation's "GPC Workstation EcoSEC-WorkStation"
[0144] Determination conditions: column temperature 40°C
[0145] Developing solvent: tetrahydrofuran
[0146] Flow rate 1.0ml / min
[0147] Standard: According to the measurement manual of the "GPC Workstation EcoSEC-WorkStation", the following monodisperse polystyrene having a known molecular weight was used.
[0148] (Using polystyrene)
[0149] "A-500" manufactured by Tosoh Corporation
[0150] "A-1000" manufactured by Tosoh Corporation
[0151] "A-2500" manufactured by Tosoh Corporation
[0152] "A-5000" manufactured by Tosoh Corporation
[0153] "F-1" manufactured by Tosoh Corporation
[0154] "F-2" manufactured by Tosoh Corporation
[0155] "F-4" manufactured by Tosoh Corporation
[0156] "F-10" manufactured by Tosoh Corporation
[0157] "F-20" manufactured by Tosoh Corporation
[0158] "F-40" manufactured by Tosoh Corporation
[0159] "F-80" manufactured by Tosoh Corporation
[0160] "F-128" manufactured by Tosoh Corporation
[0161] Sample: A solution of the curable resin obtained in Synthesis Example having a solid content of 1.0% by mass in tetrahydrofuran was filtered through a microfilter (50 μl).
[0162] (Synthesis Example: Curable Resin (a))
[0163] 48.9 g (0.4 mol) of 2,6-dimethylphenol, 272.0 g (1.4 mol) of α,α'-dihydroxy-1,3-diisopropylbenzene, 280 g of xylene and 70 g of activated clay were added to a 1L flask equipped with a thermometer, a cooling tube, a Dean-Stark trap and a stirrer, and heated to 120°C while stirring. Furthermore, the temperature was raised to 210°C while removing the distilled water with a Dean-Stark tube, and the reaction was carried out for 3 hours. Then, the mixture was cooled to 140°C, 146.6 g (1.2 mol) of 2,2-dimethylphenol was added, and the temperature was raised to 220°C, and the reaction was carried out for 3 hours. After the reaction, the mixture was cooled to 100°C in air, diluted with 300 g of toluene, the activated clay was removed by filtration, and low molecular weight substances such as the solvent and unreacted substances were distilled off under reduced pressure, thereby obtaining 365.3 g of an intermediate phenol compound. The hydroxyl equivalent (phenol equivalent) of the obtained intermediate phenol compound was 299.
[0164] In a 2L flask equipped with a thermometer, a cooling tube and a stirrer, 365.3 g of the intermediate phenol compound obtained and 700 g of toluene are added and stirred at about 85°C. Next, 29.9 g (0.24 mol) of dimethylaminopyridine is added. When it is considered that all the solids are dissolved, 277.5 g (1.8 mol) of methacrylic anhydride is added dropwise over 1 hour. After the addition is completed, the reaction is further allowed to react at 85°C for 3 hours. The reaction solution is added dropwise over 1 hour to 4000 g of methanol that has been vigorously stirred with a magnetic stirrer in a 5L beaker. The obtained precipitate is filtered under reduced pressure with a membrane filter and then dried to obtain a curable resin (a) having an indane skeleton with the following structural formula (average number of repeating units n = 1.6).
[0165] [Chemistry 7]
[0166]
[0167] <Preparation of Curable Resin Composition>
[0168] Using the curable resin (a) obtained in the above synthesis example, a curable resin composition having the blending contents (raw materials, blending amounts) described in the following Table 1 was prepared. Specifically, toluene was used as a solvent, and mixing was performed using a rotary mixer, and a varnish adjusted to 60% by mass of nonvolatile components was heated under reduced pressure (under vacuum reduced pressure, kept at 70° C. for 1 hour) to obtain a powder by desolvation.
[0169] The raw materials other than the curable resin (a) used in the curable resin composition are as follows.
[0170] Curable resin (a'): SA 9000-111 manufactured by SABIC. Modified polyphenylene ether
[0171] Compound (b1): Ricon 100 manufactured by Cray Valley Co., Ltd. Molecular weight 4,500, butadiene-styrene random copolymer containing 70% 1,2-vinyl (butadiene%) and 25% styrene
[0172] Compound (b2): Ricon 184 manufactured by Cray Valley Co., Ltd. Molecular weight 8,600, butadiene-styrene random copolymer containing 30% 1,2 vinyl (butadiene%) and 28% styrene
[0173] Compound (b3): Ricon 257 manufactured by Cray Valley Co., Ltd. Butadiene-styrene-divinylbenzene copolymer
[0174] Compound (b4): B-1000 manufactured by Nippon Soda Co., Ltd. Molecular weight 1200, butadiene homopolymer containing 85% or more of 1,2-vinyl groups
[0175] Compound (b5): TAIC. Triallyl isocyanurate
[0176] Compound (b'): tert-butylstyrene
[0177] <Production of Cured Material>
[0178] The curable resin composition was placed in a mold, heated at 200° C. for 2 hours using a press machine, and thermally cured to obtain a cured product having a thickness of 1.8 mm.
[0179] <Evaluation of Heat Resistance>
[0180] The obtained cured product was cut into a size of 55 mm in length × 5 mm in width × 1.6 mm in thickness as a test piece. The test piece was evaluated using a viscoelasticity measuring device (DMA: solid viscoelasticity measuring device "DMS 6100" manufactured by Hitachi High-Technologies Corporation, deformation mode: bending at both ends, measurement mode: sine wave vibration, frequency 1 Hz, heating rate 3°C / min), and the temperature at which the elastic modulus changes to the maximum is taken as the glass transition temperature Tg.
[0181] <Evaluation of Dielectric Properties>
[0182] In accordance with JIS-C-6481, the dielectric constant and dielectric loss tangent at 10 GHz of the test piece stored in a room at 23°C and 50% humidity for 24 hours after drying were measured using a network analyzer "E8362C" manufactured by Agilent Technologies, Inc. by the cavity resonance method.
[0183] <Sticky feeling>
[0184] The curable resin composition was touched with a finger through a rubber glove at room temperature to evaluate the presence or absence of stickiness.
[0185] A: Not sticky
[0186] B: No stickiness after short finger contact
[0187] C: Sticky
[0188] A and B are qualified, and C is unqualified.
[0189] <Varnish solubility>
[0190] The uniformity of the varnish (varnish containing 60% by mass of nonvolatile components using toluene as a solvent) in the preparation of the curable resin composition was visually evaluated.
[0191] Good: Transparent
[0192] Bad: Turbid
[0193] <Uniformity of Cured Material>
[0194] Evaluation was performed by observing the appearance of the obtained cured product.
[0195] Good: Transparent
[0196] Poor: Turbid [Table 1]
[0197]
[0198] From the evaluation results in Table 1, it was confirmed that Examples 1 to 8 were excellent in heat resistance and low dielectric properties.
[0199] On the other hand, the cured product of Comparative Example 1 lacking (B) of the present invention was brittle, and a test piece for measuring Tg and dielectric properties could not be prepared.
[0200] In Comparative Example 2 using modified polyphenylene ether instead of (A) of the present invention, the varnish was not uniformly dissolved, and in Comparative Example 3, the cured product lacked uniformity. Both cured products were brittle and test pieces for measuring Tg and dielectric properties could not be prepared.
[0201] Furthermore, compared with Comparative Example 3 in which tert-butylstyrene was blended instead of (B) of the present invention, Examples were excellent in heat resistance and also good in tackiness.
[0202] Possibility of industrial application
[0203] According to the curable resin composition of the present invention, a cured product having excellent heat resistance (high glass transition temperature) and dielectric properties (low dielectric properties) can be obtained. The cured product of the present invention can be suitable for heat-resistant components, electronic components, and can be particularly suitable for prepregs, semiconductor sealing materials, circuit boards, build-up films, build-up substrates, adhesives, and resist materials. In addition, it can also be suitable for the matrix resin of fiber-reinforced resins, and is suitable as a prepreg with high heat resistance.
Claims
1. A curable resin composition comprising a curable resin (A) having an indane skeleton represented by the following general formula (1), and a compound (B) comprising a non-conjugated vinyl group bonded to a non-aromatic ring group, [Chemical 1] In the above formula (1), X represents a (meth)acryloyl group, Ra and Rb are each independently an alkyl group, an aryl group, an aralkyl group or a cycloalkyl group having 1 to 12 carbon atoms, j represents an integer of 1 to 3, k and l each independently represent an integer of 0 to 4, n is the average number of repeating units and represents a value of 0.5 to 20, and m represents an integer of 0 to 2, wherein, The straight line from Ra, X and the carbon atom to the aromatic ring indicates that the aromatic ring can be bonded to any position on the aromatic ring.
2. The curable resin composition according to claim 1, wherein The (A) is a curable resin having an indane skeleton represented by the following general formula (2), [Chemistry 2] In the above formula (2), R1 and R2 are independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an aryl group, an aralkyl group or a cycloalkyl group, and R1 and R2 are not both hydrogen atoms at the same time. n is the average number of repeating units and represents a value of 0.5 to 20.
3. The curable resin composition according to claim 1, wherein The above-mentioned (B) is a butadiene polymer containing a 1,2-butadiene unit having a 1,2-vinyl group in a side chain in the molecule.
4. The curable resin composition according to claim 1, wherein The (B) is a compound having two or more allyl groups.
5. The curable resin composition according to claim 1, wherein The mass of (B) is 5 to 40 parts by mass based on 100 parts by mass of the total of the mass of (A) and the mass of (B). 6 . A cured product obtained by subjecting the curable resin composition according to claim 1 to a curing reaction. 7 . A varnish obtained by diluting the curable resin composition according to claim 1 with an organic solvent. 8 . A prepreg comprising a reinforcing substrate and a semi-cured product of the varnish according to claim 7 impregnated into the reinforcing substrate.
9. A circuit board obtained by laminating the prepreg according to claim 8 and copper foil and then heat-compression-bonding them.
Citation Information
Patent Citations
Monomer and oligomer having novel multiple vinylbenzyl ether groups, manufacture and cure product therefrom
JP1988068537A
Curable resin composition
JP1989065110A
Styrene-terminated thermosetting polymer of a tetrakisphenol
JP1989503238A
Polyvinylbenzyl ether compound and its production
JP1997031006A
Poly(vinylbenzyl) ether compound and method for producing the same
JP2005314556A